Risk of Parkinson’s disease in patients with neovascular age-related macular degeneration - Etminan, Mahyar (J Curr Ophthalmol, 2018)
PURPOSE: To examine the risk of developing Parkinson's Disease (PD) in patients who are newly diagnosed with neovascular age-related macular degeneration (nAMD). METHODS: This was a cohort study using the British Columbia (BC) Retinal Disease Database. Data from 2009 to 2013 was accessed. Rates of PD in patients prior to the diagnosis of nAMD were computed and compared to the rates of patients newly diagnosed with PD after the diagnosis of nAMD. RESULTS: The rate of PD prior to the diagnosis of nAMD was 1.42 per 100,000 person-years. The rate of PD after the diagnosis of nAMD was 2.88/100,000 person-years. The rate ratio was 2.03 (95% CI; 1.31–3.16). CONCLUSIONS: The findings suggest that patients who are diagnosed with nAMD are at a significantly higher risk of developing PD later in life. More studies are needed to identify the pathological mechanism between the two diseases.